IMPLEMENTASI BAHASA INDONESIA SEBAGAI IDENTITAS NASIONAL DAN SARANA PENGUATAN KARAKTER MASYARAKAT - Cecep Wahyu Hoerudin (Jurnal Kelola: Jurnal Ilmu Sosial, 2021)
The purpose of this study was to analyze the implementation of the Indonesian language as a national identity and a means of strengthening the character of the community. The writing method used in this research is descriptive-qualitative method. The type of data used in this study is secondary data collected from various literatures using the theoretical basis used is National Identity which is strongly influenced by the understanding of Ideology in politics than Patriotism and other nationalisms. Based on the results of the data and analysis, it can be seen that the function of the Indonesian language as a national identity has been implemented in various institutions, such as education, government and others. As a national identity, Indonesian language has the following functions: 1) As the official state language; 2) As the language of instruction in the world of education,; 3) Media liaison for the interest of national development; and 4) Media development of culture, and science and technology.